THE CRISIS OF MIGRATION AS THE CRUCIAL REASON OF DISINTEGRATION PROCESSES IN THE EU - Вахняк, Г. В. (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY Idea, 2019)
The article is dedicated to the analysis of the reasons of the current migration crisis’development in the European Union. The examination of the peculiarities of the migration processes and the determination of their influence on the EU political unity. The analysis of the peculiarities of implementation and realization of the common migration policy of the European countries. It was defined that the current migration crisis poses a serious threat to the political unity of the states of the European Union and the further European integration processes. The origins of the current migration crisis in Europe are related to the "Arab Spring" period, but it got significantly developed at the begging of 2015, for the reason of a huge increase in the flow of refugees and illegal migrants to the European Union from the countries of North Africa, the Middle East and South Asia, as well as the EU was not ready to receive and to distribute them. This migration crisis in Europe is considered to be the largest one since the Second World War. The migration crisis of 2015 differs from the previous ones both in the scale and for its reasons. Mostly, people who migrated were those who were trying to save their lives during civil wars in the Middle East and Afghanistan. However, not only military conflicts and the unstable situation in the world are the causes of migration movements, the asylum seekers' aspirations to get closer to the European standards and the improvement of living conditions. Today, the European Union's migration policy is carried out by such supranational institutions as the European Council; European Commission, which draws up legislative proposals; The Council of the European Union, the European Parliament, which has been mandated to decide on refugee policy since 2005. An important role is also played by non-governmental organizations. However, today one of the key issues is the issue of inconsistency between the activities of these EU political institutions and the implementation of an effective migration policy. It can be argued that the current migration crisis, provoked by the influx of refugees from the zones of hostilities, pointed to the ineffectiveness of the EU migration policy and became an unconditional challenge to ethno-political security. Terrorism acts, organized by migrants from the migrant background, which claimed the lives of hundreds of people, confirm the need for a revision of the legal settlement of migration flows in the European Union.